Comparative study of solar tracking and fixed-tilt photovoltaic modules in Morocco - Mrhar, Oumaima; Kandoussi, Khalid; Eljouad, Mohamed; Sellami, Assia (European physical journal. Applied physics, 2022)
Nowadays the global energy context is being difficult, looking for other alternatives is obviously observed in many countries, and the expectations in terms of renewable energies are increase continuously. Taking the example of photovoltaic energy with its environmental advantages and especially the fixed-tilt solar panel. This technology is used to optimize radiation received, and more the surface of a solar panel is perpendicular to incident rays, more the efficiency is better, hence the objective of our work. In this context, a comparative study between a fixed-tilt panel and a panel with a 2-axis Open Loop tracking system is performed for the first time in AFRICA, and exactly in the 6 regions of MOROCCO distributed according to their solar potential. The comparative study is done on Matlab/Simulink software, in which the incident radiation for both systems is calculated from a radiation model based on zenith and azimuth angles obtained via the Solar position algorithm; the photovoltaic power is also calculated in our program. As a results, we found that the use of open-loop solar tracking systems in less sunny areas and periods increase the productivity of photovoltaic panels and consequently improves its energy efficiency.